San Francisco Museum of Modern Art 1997-98 : A Fiscal Year Report. - McKeon, Elaine; Ross, David A.; SFMOMA (San Francisco Museum of Modern Art) San Francisco (San Francisco : SFMOMA (San Francisco Museum of Modern Art), 1999)
Hadid, Zaha ; Hesse, Eva ; Hill and Adamson ; Johnson, Sergent ; Kiefer, Anselm ; LeWitt, Sol ; Logan, Kent ; McQueen, Steve ; Mondriaan, Piet ; Newman, Barnett ; Orozoco, Gabriel ; Rauschenberg, Bob ; Rauschenberg, Robert ; Ross, David ; Stauter, Susan ; Wild, Lorraine
Engels
boek